Pregnant mothers’ knowledge, attitude and practice towards preventions of iron deficiency anemia in Harar town, Ethiopia - Abdu Oumer Abdu; Arif H. Hussein (Intelektual Pustaka Media Utama, 2019)
Low maternal risk perception, poor dietary practice and low adherence to iron and folate tablets among pregnant women are major contributors for higher burden of anemia. Iron deficiency anemia contribute to more than half of Anemia among pregnant women. Thus the level of maternal awareness and attitude towards dietary and other prevention practices of anemia are not well established in the study area. This study was to assess knowledge, attitude and practice of pregnant mothers towards the prevention of iron deficiency anemia in Ethiopia, 2018. Hospital based cross sectionals study was conducted on randomly selected, 128 pregnant mothers attending antenatal care service in Harar town. Data were collected by health professionals using pre tested questionnaire containing socio demographic, knowledge, attitude and practice related questions. Attitude questions were organized in five Likert scale from strongly disagree to strongly agree using positive statements. Similarly, practices were assessed in yes/no (appropriate practices were scored as yes or no otherwise). Data was analyzed using SPSS version 20 using frequency, tables, graphs and means. Pearson correlation with r was used to assess the relationship between knowledge, attitude and practice. Analysis of Variance was used to compare the mean practice by different factors. Knowledge, attitude and practice of pregnant women on preventions of IDA are not satisfactory. Thus poor practice towards prevention of IDA is the main contributing factor for high burden of anemia.